Long Non-coding RNA EPIC1 Promotes Cell Proliferation and Motility and Drug Resistance in Glioma - Wang, Jianjiao (Mol Ther Oncolytics, 2020)
Evidence has revealed that long non-coding RNAs (lncRNAs) are involved in carcinogenesis and tumor progression. lncRNAs play an important role in regulation of numerous cellular processes including cell proliferation, apoptosis, cell cycle, differentiation, and motility. Several studies have demonstrated that lncRNA EPIC1 governs cell growth, cell cycle, migration, invasion, and drug resistance in human malignancies. However, the role of EPIC1 and its underlying molecular mechanisms in glioma have not been investigated. In this study, we determined the function of EPIC1 in glioma cells via upregulation or downregulation of EPIC1. We further dissected the mechanism of EPIC1-mediated tumor progression in glioma. Our results showed that inhibition of EPIC1 suppressed cell viability, induced apoptosis, inhibited cell invasion, and increased cell sensitivity to temozolomide in glioma cells. Consistently, overexpression of EPIC1 exhibited the opposite effects in glioma cells. Moreover, our data suggest that EPIC1 exerts its biological functions via targeting Cdc20 in glioma cells. In line with this, overexpression of Cdc20 reversed the EPIC1-mediated tumor progression in glioma cells. Therefore, targeting EPIC1 might be a useful approach for glioma treatment.